STUDIES ON THE AGE AND GROWTH OF THE MALABAR SOLE, CYNOGLQSSUS SEMIFASCIATUS, DAY - Seshappa, G; Bhimachar, B S (Indian Journal of Fisheries, 2016)
FOR the development of a scientific management policy for any fishery, it is essential to know among other things, the rate of growth of the species concerned and the changes in the age-composition of its stocks from season to season and from year to year. The present paper deals with the results of investigations which were designed to collect information on these two aspects in relation to the Malabar sole, Cynoglossus semifasciatus. Although this forms a valuable fishery along the Malabar Coast no attention has been paid in the past to a detailed investigation of its biology